Efficacy assessments of public artworks intervening in rural built environments for tourism developments: a comparative study of two tourism villages in Hangzhou - Xuguang Zhu; Chaonan Shen; Tianjie Li (Journal of Asian Architecture and Building Engineering)
Interventions through rural tourism programs and rural art projects have played a significant role in rural revitalization initiatives in China, wherein public artworks have been deliberately integrated into rural built environments. This study combined both objective and subjective measurements, in two representative tourism villages in Hangzhou that underwent revitalizations. These artworks were strategically placed in the public domains of the villages in two distinct phases, enabling the calculation of their Visual Exposure Rates (VERs). Objective evaluations were gathered on-site via the Comprehensive Assessment of Artworks and Surroundings (CAAS) survey, and the data were subjected to quantitative analysis using the Analytic Hierarchy Process (AHP) method. The study reveals differential changes in VERs across the two villages, concurrently observing variations in the CAAS scores. Findings indicate the efficient promotion of fusion design to support sustainable rural tourism in three dimensions: spatial layout characteristics, cultural and aesthetic values, and tourism management practices. It suggested that sustainable rural tourism development should not hinge solely on increasing the quantity of public artworks but rather on the holistic improvement of sustainable spatial design and management to enhance the rural value chain, ensuring a more comprehensive and sustainable tourism experience